Impossible naso-tracheal intubation In a patient with isolated mandibular injury: A case report - Ayten Saracoglu (8075222) (2023)
Airway management is one of the cornerstones of multidisciplinary treatment for patients with maxillofacial trauma. Nasal intubation is a technique used in maxillofacial procedures to provide space for surgery in the oral cavity. However, in some patients, it cannot be applied due to midface trauma, and in anatomical variations of the nasal septum it may even be impossible. In this case report, we aimed to present the airway management of a patient with type VI septum deviation according to Mladina classification, focusing on our step-by-step assessment in line with anticipated difficult airway guidelines with emphasis on non-technical skills. Other Information Published in: Trends in Anaesthesia and Critical Care License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1016/j.tacc.2023.101301